Percepción de asimetrías faciales entre estudiantes de pregrado y posgrado de ortodoncia de la Facultad de Odontología de la Universidad de las Américas - Males Cifuentes, Carlos David (2020)
Introduction: the diagnosis of facial asymmetries is a fundamental aspect in the evaluation for an orthodontic treatment, because a bad treatment can lead to unfavorable results. Objectives: To compare the perception of facial asymmetries among undergraduate and graduate students of Orthodontics of the Universidad de las Américas, by survey. Materials and Methods: frontal images of male and female patients without smiling, with 0 degrees, 2 degrees, 4 degrees, 6 degrees and 8 degrees alteration for facial asymmetries of the lower third of the face were presented to the participants, so they could select asymmetries according to their perception of the degree of chin and the lip commissures deviation, which can be: none, mild, moderate, severe or very severe; In addition, images with different degrees of deviation were presented to determine facial attractiveness and the need for treatment of the patients. Results: a greater statistical significance was found for graduate students in relation to undergraduate students, since in the chin deviation the graduate students correctly indicated the deviations none, mild, severe and very severe, whereas the students of undergraduates correctly noted moderate deviation; in the deviation of the labial commissure, the graduate students presented correct answers in all the degrees of deviation raised in relation to the undergraduate students in relation to the percentage of correct answers, finding values not very distant from each other; Regarding facial attractiveness and need for treatment, similar results were found between undergraduate and graduate students in the deviations presented, without too much statistical difference. Conclusions: graduate students were more successful in pointing out the different degrees of asymmetry in both the male and female patients than undergraduate students.